Origin and domestication of cole crops (Brassica oleracea L.): Linguistic and literary considerations - Maggioni, Lorenzo; Bothmer, Roland von; Poulsen, Gert; Branca, Ferdinando (Springer, 2010)
Contrasting hypotheses have been made to locate the area of domestication of Brassica oleracea crops (i.e., cole crops), suggesting either a North Atlantic or a Mediterranean origin. In the absence of archaeological proof, linguistic and literary considerations can offer some insight into this issue. This paper gathers information from the linguistic, literary, and historical points of view that are compatible with the domestication of B. oleracea in the ancient Greek-speaking area of Central and East Mediterranean.